High Prevalence of Abacavir-associated L74V/I Mutations in Kenyan Children Failing Antiretroviral Therapy. Issue 8 (August 2017) - Dziuban, Eric J.; DeVos, Joshua; Ngeno, Bernadette; Ngugi, Evelyn; Zhang, Guoqing; Sabatier, Jennifer; Wagar, Nick; Diallo, Karidia; Nganga, Lucy; Katana, Abraham; Yang, Chunfu; Rivadeneira, Emilia D.; et al.
Abstract : Abstract: A survey of 461 HIV-infected Kenyan children receiving antiretroviral therapy found 143 (31%) failing virologically. Drug resistance mutations were found in 121; 37 had L74V/I mutations, with 95% receiving abacavir (ABC)-containing regimens. L74V/I was associated with current ABC usage ( P = 0.0001). L74V/I may be more prevalent than previously realized in children failing ABC-containing regimens, even when time on treatment has been short. Ongoing rigorous pediatric drug resistance surveillance is needed.